Values Driving Organic Food Purchase Intention: A Comparative Analysis between a Developing Eastern Country (Iran) and a Developed Western Country (US). Issue 4 (8th August 2019) - Shahriari, Elmira; Torres, Ivonne M.; Zúñiga, Miguel Angel; Yarlou, Payman Mohammad
Abstract: This study examines the salient organic food related values driving consumers' attitude and purchase intentions in a developing country (Iran) and a developed country (US). Additionally, we explain and compare the role of subjective norms in organic food purchase intention between these countries. To examine, the organic food values and patterns of consumers' organic food choices, we collected data from 217 and 210 respondents in Iran and the US, respectively. Our findings show that "Price" in Iran and "Authenticity/naturalness" in the US were the strongest predictors of attitude toward the organic food. Eating culture, consumer's knowledge, perceptions, and concerns in society could be the underlying reason for the differences in importance of values between two societies. We also found the relationship of subjective norms with purchase intention varies across societies. At the end of this study, we discuss the implications for international marketing campaigns and for policy makers in each country.